An empirical investigation into the major drivers of corporate social responsibility - Azlan Amran, Karpal Singh Dara Singh, Md. Aminul Islam, Essia Ries Ahmed (Opción, 2019)
This paper reviews and examines major drivers that were able to compel Malaysian organizations to adopt corporate social responsibility (CSR) practices. An instrument consisting of CSR drivers and CSR practices was developed and a survey was conducted targeting Malaysian consumers with a sample of 1440 respondents that were selected across 12 states of West Malaysia. The results revealed that all six drivers had an effect on CSR practices which implied that these drivers were able to influence organizations in Malaysia to adopt CSR practices. It can be concluded that customers generally expect organizations to commit themselves to CSR